2016
DOI: 10.1002/chem.201602377
|View full text |Cite
|
Sign up to set email alerts
|

Alkyltelluro Substitution Improves the Radical‐Trapping Capacity of Aromatic Amines

Abstract: The synthesis of a variety of aromatic amines carrying an ortho-alkyltelluro group is described. The new antioxidants quenched lipidperoxyl radicals much more efficiently than α-tocopherol and were regenerable by aqueous-phase N-acetylcysteine in a two-phase peroxidation system. The inhibition time for diaryl amine 9 b was four-fold longer than recorded with α-tocopherol. Thiol consumption in the aqueous phase was found to correlate inversely to the inhibition time and the availability of thiol is the limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…90 %d euteration grade) or an iodine substituent were introduced at the ortho-phenyl position (Scheme 5, left). [25][26][27][28] In summary,w eh ave shown that highly selective single and double ortho-CH activation reactions of diphenylamide, (NPh 2 ) À ,a re feasible upon incorporation of this ligand into ac ationic bismuth complex. [23] Current routes to orthoiododiphenylamines (related to 4b)r ely on palladium catalysis and comparatively forcing conditions (100 8 8C, 24 h) or the use of benzyne precursors.…”
Section: Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…90 %d euteration grade) or an iodine substituent were introduced at the ortho-phenyl position (Scheme 5, left). [25][26][27][28] In summary,w eh ave shown that highly selective single and double ortho-CH activation reactions of diphenylamide, (NPh 2 ) À ,a re feasible upon incorporation of this ligand into ac ationic bismuth complex. [23] Current routes to orthoiododiphenylamines (related to 4b)r ely on palladium catalysis and comparatively forcing conditions (100 8 8C, 24 h) or the use of benzyne precursors.…”
Section: Communicationsmentioning
confidence: 99%
“…[11] In main-group chemistry,t he reaction of HNPh 2 with nBuLi in a3 :7 stoichiometry afforded the more complicated cluster [(Ph 2 NLi)[Ph(C 6 H 4 Li)NLi] 2 (nBuLi) 2 (Et 2 O) 4 ], containing two ortho-metalated diphenylamide groups,a fter af ew days. 28(2) ). [13,14] Under optimized reaction conditions, 2 crystallized directly from the reaction mixture at 23 8 8Ca fter about 16 h, and was isolated in 91 %overall yield as ayellow solid.…”
mentioning
confidence: 99%
“…The experimental setup for determination of the rate of NAC-consumption in the two-phase lipid peroxidation model was recently described. 13 The values reported are means ± SD based on triplicates.…”
Section: 5´-tellurobis--tocopherol (9)mentioning
confidence: 99%
“…1 H, 13 C and 125 Te NMR data for all new compounds prepared. This material is available free of charge via the Internet at http://pubs.acs.org.…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation